Communication Resource Planning for Monitoring and Control Systems Based on Distributed Virtual Instrumentation Networks. (2016) - Turc, Traian; Gligor, Adrian
Abstract: Distributed monitoring and control systems based on distributed virtual instrumentation networks consist of numerous components, ranging from field sensors to monitoring and control modules, which are potentially spread across a wide geographical area. This configuration requires a communication infrastructure to facilitate both physical and logical connectivity. In this paper, we tackle the challenge of planning communication resources that is in correlation with important topics such as: fast development, dependability and service availability. Our discussions, conclusions and recommendations are based on an experimental platform developed in LabView. Our investigations pursue designing an optimal communication infrastructure and choosing the right communication bandwidth.